Efeitos da suplementação dietética com farinha de banana verde na doença renal crônica experimental - Matheus, Marco Aurelio Costa [UNIFESP] (2019)
Introduction: Changes in food and social behavior in populations of industrialized countries have led to the emergence of chronic diseases such as chronic kidney disease (CKD), considered to be poor in the 21st century, mainly due to its asymptomatic onset and deleterious evolution. Increased diligence for a healthier life, especially with increasing access to information, leads individuals to greater understanding of the importance of a balanced and functional diet in order to have a better quality of life and to mitigate the possibility of the result of lifestyle. In addition, subjects who already have, for example, CKDs and have dietary restrictions, can gain access to a wider range of foods that, in addition to nutritional value, will interfere in order to compensate for the progression of the disease. Objective: To demonstrate the efficiency of resistant starch present in green banana meal as a therapeutic adjunct in experimental chronic kidney disease. Material and Methods: C57BL / 6 mice from 6 weeks of life were subdivided into 4 groups: SHAM not supplemented, SHAM supplemented, chronic non-supplemented kidney disease, and chronic kidney disease supplemented. The animals were supplemented with green banana meal in the proportion of 10% of the total diet, containing 5g of resistant starch added to feed for 4 weeks. The animals were weighed weekly for monitoring of weight gain and 24 hours after surgery for weight loss analysis. Urine and feces were collected every week. In the third week, the animals underwent unilateral ureter obstruction surgery to cause renal damage, mimicking a CKD picture. One week after surgery, the animals were euthanized and collected: blood, kidney, urine from the renal pelvis, epididymal fat, large intestine and feces. Biochemical analyzes were performed for creatinine and urine and serum urea, albuminuria by ELISA and electrophoresis. Picrosírius of histological sections of kidney to evaluate the collagen deposition in the interstitium of renal tissue, immunohistochemistry to evaluate the proliferation of fibroblasts. We also carried out analyzes by fluorescence in situ hybridization in a CONFOCAL microscope to analyze the mucus layer and to determine the relationship between bacteroidetes and firmicutes. Short chain fatty acids were dosed in the faeces to quantify each type. Indirect calorimetry was measured in the third week to measure the metabolic patterns of the animals. Results: Regarding the weighing of the animals, the groups did not present differences in weight gain, only in weight loss after surgical procedure where supplemented animals were less affected. The weight of the epididymal fat did not present statistical difference, however, it showed a slight tendency to lower values in the supplemented animals. The relation body weight x epididymal fat also did not represent statistically significant alterations. Urinary creatinine showed a marked increase in the operated animals, with a small decrease in the animals with chronic renal disease and supplemented. Serum urea in the groups remained similar to each other, except for the supplemented control group that obtained a slight decrease. When we evaluated serum creatinine, the supplemented groups represented higher values in the groups with chronic and control renal disease. In the albuminuria test, the control groups represented values much lower than the chronic kidney patients. In the group with renal disease, the supplemented animals represented a small tendency to decrease, without statistical significance. When analyzing picrosirius, we observed that the supplemented animals had lower deposition of collagen in renal tissue, indicating that these animals were more protected than those not supplemented. In the immunohistochemistry analysis the stained slides for FSP1 demonstrated that the supplemented animals had smaller numbers of fibroblasts in the renal tissue studied. The mucus layer analysis in the animals that had dietary supplementation obtained greater thicknesses in the layers of intestinal mucus than the non-supplemented ones, indicating that the banana flour promoted benefits for these animals. The relation bacteroidetes and firmicutes was also analyzed and the genus of bacteroidetes bacteria was predominant in the supplemented animals, whereas firmicutes, was expressive in animals that consumed the ration without supplementation. The short chain fatty acids showed a significant increase, mainly for acetate followed by butyrate in the supplemented animals, indicating that these animals had greater access to these short chain fatty acids. Indirect calorimetry indicated that the animals that were supplemented had a higher basal metabolic rate, so they took better advantage of the energy released by the supplemented feed. Conclusion: Dietary supplementation with green banana flour promoted several benefits, both for intestinal microbiota and for the kidney in animals with chronic renal disease induced, showing a promising therapeutic adjuvant for this type of disease.